Occurrence, Pathogenic Potential and Antimicrobial Resistance of Escherichia coli Isolated from Raw Milk Cheese Commercialized in Banat Region, Romania - Kálmán Imre; Alexandra Ban-Cucerzan; Viorel Herman; Khalid Ibrahim Sallam; Romeo Teodor Cristina; Samir Mohammed Abd-Elghany; Doru Morar; Sebastian Alexandru Popa; Mirela Imre; Adriana Morar (Antibiotics, 2022)
The aim of the present study was to investigate the presence, pathogenic potential and antimicrobial susceptibility profile of Escherichia coli isolated from raw milk cheese, traditionally produced by farmers and marketed directly to the consumer in Banat region, Romania. A total of 81.1% (43/53) of the processed samples expressed positive results for E. coli, with a distribution of 83.8% (31/37), and 75.0% (12/16) in the cow- and sheep-milk-origin assortments, respectively. Overall, 69.8% (30/43) of the specimens had a contamination level ≤10 CFU/g. Molecular tests showed that, from the total number of E. coli isolates, 9.3% (4/43) harbored the stx2, and 2.3% (1/43), the stx1 virulence genes. The E. coli O157 (including H7) biovariety was identified in 7% (3/43) of the samples by the Vidas equipment. From the 27 antimicrobials tested with the Vitek2 automated system, the E. coli isolates displayed resistance to enrofloxacin (100%, 15 out of 15 tested isolates), ampicillin (39.5%, 17/43), norfloxacin (28.6%, 8/28), fosfomycin (25%, 7/28), amoxicillin/clavulanic acid (23.3%, 10/43), cefalexin (20%, 3/15), cefalotin (13.3%, 2/15), tetracycline (13.3%, 2/15), trimethoprim-sulfamethoxazole (9.3%, 4/43), piperacillin-tazobactam (7.1%, 2/28), cefotaxime (7.1%, 2/28), cefepime (7.1%, 2/28), ticarcillin/clavulanic acid (6.7%, 1/15), florfenicol (6.7%, 1/15), ceftazidime (3.6%, 1/28), and ertapenem (3.6%, 1/28). Ten (23.3%) strains were multidrug-resistant. The obtained preliminary results indicated hygienic–sanitary deficiencies throughout the cheese production process, and demonstrated that these products can harbor virulent and multidrug-resistant E. coli strains, which constitute a public health risk. However, future investigations, processing a higher number of samples, are still necessary to draw comprehensive conclusions.